Love me, don't leave me overcoming fear of abandonment & building lasting, loving relationships - Skeen, Michelle (Oakland, California New Harbinger Publications, Inc., 2012)
"Everyone thrives on love, comfort, and the safety of family, friends, and community. But if you are denied these basic comforts early in life, whether through a lack of physical affection or emotional bonding, you may develop intense fears of abandonment that can last well into adulthood-fears so powerful that they can actually cause you to push people away. If you suffer from fears of abandonment, you may have underlying feelings of anger, shame, fear, anxiety, depression, and grief. These emotions are intense and painful, and when they surface they can lead to a number of negative behaviors, such as jealousy, clinging, and emotional blackmail. In Love Me, Don't Leave Me, therapist Michelle Skeen combines acceptance and commitment therapy (ACT), schema therapy, and dialectical behavioral therapy (DBT) to help you identify the root of your fears. In this book you'll learn how schema coping behaviors-deeply entrenched and automatic behaviors rooted in childhood experiences and fears-can take over and cause you to inadvertently sabotage your relationships. By recognizing these coping behaviors and understanding their cause, you will not only gain powerful insights into your own mind, but also into the minds of those around you. If you are ready to break the self-fulfilling cycle of mistrust, clinginess, and heartbreak and start building lasting, trusting relationships, this book will be your guide"--
"Fears of abandonment can give rise to feelings of anger, shame, fear, anxiety, depression, and grief. These emotions are intense and painful, and when they surface they can lead to a number of negative behaviors, such as jealousy, clinging, and emotional blackmail. In Love Me, Don't Leave Me, therapist Michelle Skeen combines acceptance and commitment therapy (ACT), schema therapy, and dialectical behavioral therapy (DBT) to help readers identify the root of their fears so they can build lasting, trusting relationships"--
101986
Keywords: Love; Interpersonal relations; Acceptance and commitment therapy; Family & Relationships -- Love & Romance; Family & Relationships -- Emotions; Family & Relationships -- Interpersonal Relations